Source-sink limitations for grain weight in wheat and barley under waterlogging conditions during pre-anthesis - Becheran, Daniela Evangelina (2021)
In wheat and barley, grain yield is strongly affected by waterlogging, especially during the period immediately previous to anthesis. Although waterlogging reduces grain yield mainly by reductions in grain number, mean grain weight (MGW) is also frequently reduced. The aim of this work was to determine whether increases in the source-sink ratio produces smaller reductions in MGW due to waterlogging in wheat and barley. Two experiments were carried out combining a waterlogging condition 20 days pre-anthesis, two soil N conditions at sowing and source-sink manipulations during grain-filling (untrimmed or 50% trimmed spikes). Waterlogging reduced MGW in both species up to 35% in wheat and 44% in barley. The negative effect of waterlogging on MGW was intensified with warmer temperatures and higher atmospheric demand. Increases in the source-sink ratio during the grain-filling period (by trimming treatments) showed a positive impact on MGW in wheat (up to 40%) and barley (up to 20%) under waterlogging conditions. For both species, grain weight response to increases in source-sink ratio was higher at lower grain weight and/or spike hierarchies (i.e. spikes from tillers). Our results showed that waterlogging during pre-anthesis affected grain weight through a reduction in the source during grain-filling and a possible impact on potential grain weight, depending on the intensity of the stress.